Women and militancy : South Asian complexities - Mohsin, Amena; Ahmed, Imtiaz, 1958- (Dhaka : University Press Limited, 2011)
Chiefly with reference to Bangladesh; also includes Meghalaya, India.
Includes bibliographical references and index.
Keywords: Women -- Violence against -- Bangladesh; Women -- Violence against -- Meghalaya; Ahmadiyya -- Bangladesh